2017
DOI: 10.1071/en17133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of episodic rainfall on aqueous metal mobility from historical mine sites

Abstract: Environmental contextEpisodic extreme rainfall events may affect metal dynamics in rivers flowing within historical metal mining areas. This study provides an analysis of the water chemistry and geochemical processes associated with mobilisation of metals during episodic rainfall events. Findings could be used to assess the environmental quality of streams draining spoil waste areas with similar geochemical conditions, and thereby be used to guide future management strategies. AbstractThe increasing frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…This is consistent with the results of Gozzard et al, who reported that sub-watershed nonpoint sources were of little importance in the low-water season, with point source human water discharge dominating instream concentration and load [55]. This is an effective way to arrange industrial water discharge during the precipitation period, reducing the effect on the aquatic environment since the large water quantity can effectively dilute the pollutants [56].…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the results of Gozzard et al, who reported that sub-watershed nonpoint sources were of little importance in the low-water season, with point source human water discharge dominating instream concentration and load [55]. This is an effective way to arrange industrial water discharge during the precipitation period, reducing the effect on the aquatic environment since the large water quantity can effectively dilute the pollutants [56].…”
Section: Discussionsupporting
confidence: 89%
“…for Zn, LWS14, LWS17 and LWS 18 for Mn, LWS15 and LWS16 for Pb and LWS02 – LWS18 for Fe. This is suggestive of the influence of diffusion on the concentrations of these metals, and in consonance with the view that episodic rainfall mobilises aqueous metals from regions of higher concentrations to lower concentrations (Valencia-Avellan et al., 2017). This observation is in contrast with that of Yao et al.…”
Section: Resultssupporting
confidence: 82%
“…This decrease in water pH may be compensated by the loss of calcium from the loams due to leaching by rainwater, usually having a slightly acid reaction (pH = 5.4) [63], as suggested by the high content of this element in the surface sediment stratum. The leaching of Ca may be accompanied by an acceleration of metal mobilization and, after the exhaustion of the mobile part of metals from the surface strata, the process may be of a lower intensity, which will mainly be related to local rainfall, as observed in similar post-mining areas [64][65][66]. Overall, the processes of metal mobilization in the Biała valley seems to be hampered by the thick loams of low permeability strata covered by organic matter which is able to preclude access to oxygen by lower sediment strata [42].…”
Section: Metal Mobility-perspectivesmentioning
confidence: 99%